Altered neuronal activity in the visual processing region of eye-fluke-infected fish. Issue 1 (16th January 2021) - Stumbo, Anthony; Poulin, Robert; Ruehle, Brandon
Abstract: Fish, like most vertebrates, are dependent on vision to varying degrees for a variety of behaviours such as predator avoidance and foraging. Disruption of this key sensory system therefore should have some impact on the ability of fish to execute these tasks. Eye-flukes, such as Tylodelphys darbyi, often infect fish where they are known to inflict varying degrees of visual impairment. In New Zealand, T. darbyi infects the eyes of Gobiomorphus cotidianus, a freshwater fish, where it resides in the vitreous chamber between the lens and retina. Here, we investigate whether the presence of the parasite in the eye has an impact on neuronal information transfer using the c-Fos gene as a proxy for neuron activation. We hypothesized that the parasite would reduce visual information entering the eye and therefore result in lower c-Fos expression. Interestingly, however, c-Fos expression increased with T. darbyi intensity when fish were exposed to flashes of light. Our results suggest a mechanism for parasite-induced visual disruption when no obvious pathology is caused by infection. The more T. darbyi present the more visual stimuli the fish is presented with, and as such may experience difficulties in distinguishing various features of its external environment.